Soil phosphorus availability, dynamic and speciation in long-term high fertilized soils - Reis, Josimar Vieira dos (2020)
Soil tests that determine the amount of Phosphorus (P) in the soil that is available to crops have been developed over the past decades. In Brazilian soils, the extractants Mehlich-1 (M1) and Ion Exchange Resin (IER) are more commonly used. Although the Mehlich-3 (M3) soil test is widely adopted as official extractant for P and other nutrients in many countries, in Brazil most researches involving this extractant only addresses the correlation phase. Besides soil tests for P availability, the chemical fractionation of soil P is one of the main analyzes used to obtain information about the solubility of the different forms of P in soil and their availability to plants, but do not determine the species of P present in the soil. The use of the X-ray absorption near-edge structure (XANES) technique has generated important information about the soil P speciation and can complement the information generated with chemical fractionation. Therefore, our overarching goal is this study is to improve the use and recommendation of P fertilizers on highly weathered Brazilian soils in order to optimize P use efficiency while minimizing any adverse environmental impacts. This can be achieved by combining research results ranging from the most basic level, but extremely important for rational fertilizer use, such as correlation and calibration experiments, with results from more refined techniques such as chemical fractionation and speciation by XANES. To achieve these objectives we collected 10 soil samples from uncultivated and cultivated areas in different regions of Brazil. Besides, two successive cultivation of maize in 2.0 dm3 plastic pots were carried out under greenhouse conditions. The treatments consisted of a 10 × 6 factorial, 10 soil samples and six doses of P, with four replicates in a completely randomized design. The source of P was a mixture composed of 70 % of Triple Superphosphate and 30 % of Bayovar. After each cultivation, soil P was extracted by M1, M3, and IER and correlated with maize shoot dry matter yield, shoot P content, and shoot total amount of P. The results of the bioavailability experiment was used in extractants correlation and calibration works. In the original soil samples, we have determined the soil P pools by chemical fractionation and soil P species by P K-edge XANES. The highest soil P contents and the best correlations were obtained with IER. The magnitude of the correlation coefficients indicates that the three soil tests can be used to determine the availability of P in cultivated soils and that M1 could be replaced by M3. The M1 and M3 extractants were sensitive to soil phosphorus buffering capacity. Thus, the use of M3 in tropical soils is dependent on an interpretation table that stratifies the values based on a measure of soil phosphate buffer capacity, preferably the remaining phosphorus (P-rem). After two decades of soil cultivation, there were evident increase mainly in the moderately labile and non-labile P fractions, with P adsorbed mainly onto Goethite, Hematite, and Gibbsite. This suggests the accumulation of a large amount of P in the soil, contributing to the legacy P, which may play an important role buffering the most labile pools in the medium term.